Career Decision Making Self-Efficacy Mediator Antara Dukungan Kontekstual Dan Adaptabilitas Karier - Shavira Alissa; Sari Zakiah Akmal (Program Studi bimbingan Konseling PPs UNM Makassar, 2019)
The final year students are in a transition period from college to work life, their personal characteristics and support from others would enhance their career adaptability. This study aimed to examine the role of contextual support for career adaptability in final year students mediated by career decision making self-efficacy (CDMSE). 270 final year students were participated in this study, obtained by using quota sampling technique which each region of JABODETABEK was represented by 30 people. Quantitative research methods applied in this study. The measuring instruments included Career Adaptability Ability Scale (CAAS), Contextual Support and Career Decision Making Self-Efficacy Scale-Social Affirements (CDMSESAF). The analysis was conducted using a mediation test and obtained results that contextual support contributed to career adaptability mediated by CDMSE (p <0.05). In order to improve the career adaptability, the person must have a confidence in his career choices first which can be determined by the amount of contextual support that is obtained.